Counseling resilience framework for urban poor single mothers during disasters - Yague, Eileen Kaye S.; Gomez, Marie Grace A.; Cometa-Lamberte, Hazel S.; Javiniar, Joel C.; Magbata, Elizabeth Vivien S.; Olegario, Lizamarie (Quezon City College of Education, University of the Philippines Diliman, 2025)
Single mothers are more likely to suffer from physical and mental burnout as a result of the COVID-19 pandemic, the frightening number of positive cases, and the economy's downturn. They are also under stress to meet their children's needs while navigating numerous community quarantines. This study investigates the meaning of resilience for urban poor single mothers, their stressors and challenges, and the external and internal factors that contribute to resilience during disasters. It also proposes a guidance program that is tailored to their current circumstances.

In-depth interviews were conducted among 12 single mothers in urban poor communities in Ermita Malate, Manila. The study identified three meanings of resilience among single mothers: having courage, valuing family, and having positive thinking. The results also indicated that financial issues caused by job loss were the main challenge and cause of stress for single mothers, which resulted in the inability to meet their daily needs.

Additionally, love for their children, optimism, courage, resourcefulness, and spirituality were identified as the internal strengths, while support from significant people, friends, community, non-governmental organizations, and government were the external strengths

A strength-based guidance program proposal, which aims to enhance urban poor single mothers' resilience while focusing on their positive traits and strengths, is created based on the study's results. It is also recommended that LGUs and government agencies create programs to help urban poor single mothers access essential resources such as emergency financial assistance, medical care, and health and well-being support, which are crucial for gender equality and social justice.
Thesis
Includes bibliographical references (100-114 leaves)
Keywords: Single mothers -- Counseling of -- Philippines -- Malate (Manila).; Single mothers -- Philippines -- Malate (Manila) -- Social condition; Urban poor -- Philippines -- Malate (Manila).